I Can be All Three - Alikhan, Salima; Sofi, Noor (New York : Simon & Schuster Books for Young Readers, 2023)
"On Multicultural Day at school, a young girl cannot decide whether to showcase her father's Indian heritage, her mother's German heritage, or her American identity, then realizes she can highlight all three"--
Keywords: Identity (Philosophical concept) -- Juvenile fiction; Families -- Juvenile fiction; Cultural fusion -- Juvenile fiction; Identity -- Fiction; Family life -- Fiction; Cultural fusion -- Fiction